Catalytic activity of natural Cu- and Ni-containing zeolites in deep oxidation of hydrocarbons; 1st International School-Conference on Catalysis for Young Scientists. Catalyst Design, Novosibirsk, December 2-6, 2002 : abstracts - Kryazhov A. N.; Smolentseva E. V.; Kazantseva L. K.; Karpenko V. I.; Pestryakov A. N. Aleksey Nikolaevich; Ozhereliev O. A. (2002, 2002)
В фонде НТБ ТПУ отсутствует